Fluid Flow and Distributive Mixing Analysis in the Cavity Transfer Mixer. Issue 3 (15th January 2018) - Grosso, Giovanna; Hulsen, Martien A.; Overend, Andrew; Anderson, Patrick D.
Abstract: In the polymer industry good mixing is essential to guarantee the characteristics of finished products. However, optimizing mixing devices is often difficult because mixing mechanisms are the result of the complex interaction between the moving elements and the non‐Newtonian fluids used. Full 3D simulations are computationally expensive and the complexity of the problem is often split into approximated subproblems. The present work focuses on a simplified 2D model of the Cavity Transfer Mixer, investigating stretching and folding mixing actions. Several geometrical and functioning parameters, such as cavity speed, cavity shape, intercavity distance, rotor–stator clearance, and fluid rheology are varied. Mixing is analyzed in terms of Poincaré maps and by simulating the evolution of fluid blobs. The intercavity distance is found to play a major role, enabling and governing the stretching actions inside the mixing device. Abstract : The present work proposes a model and a study of fluid flow and mixing in a simplified 2D cavity mixer (inspired by the Cavity Transfer Mixer) and investigates the effect on mixing of several geometrical and functioning parameters. Mixing is analyzed in terms of Poincaré maps and by simulating fluid blob evolutions during mixing.